Health Belief Model for the Analysis Factors Affecting Community Acceptance of COVID-19 Vaccination Dose II in Oenggae Village, Pantai Baru Subdistrict, Rote Ndao, East Nusa Tenggara - Herpri Astince Batukh; Amelya B. Sir; Sigit Purnawan (Journal of Health Promotion and Behavior, 2024)
Background: Efforts to reduce transmission of COVID-19 by carrying out COVID-19 vaccinations. The COVID-19 vaccination coverage in Rote Ndao is 52.92%. Oenggae Village is included in the working area of the Korbafo Health Center which has the lowest dose II COVID-19 vaccination coverage, namely 41.76%. This study aimed to analyze the relationship between the Health Belief Model (HBM) theoretical approach and community acceptance of the COVID-19 Dose II vaccination in Oenggae Village, Pantai Baru District, Rote Ndao in 2022. Subjects and Method: An observational analytic study with a cross-sectional design was conducted in Oenggae Village, Pantai Baru District, Rote Ndao from December 2022 to January 2023. A total of 107 people aged 6->55 years were selected for this study. The dependent variable is people's acceptance of the second dose of COVID-19 vaccination. The independent variables are perceived vulnerability, perceived severity, perceived benefits, perceived barriers and cues to act. Data was collected using a questionnaire. Data were analyzed by chi-square test. Results: Perceived vulnerability is high (OR= 3.91; 95 CI= 1.70 to 9.03; p= 0.002), perceived severity is high (OR= 10.59; 95% CI= 3.27 to 34.25; p< 0.001), perceived benefit is high (OR= 11.27; 95) % CI= 1.33 to 94.94; p= 0.009), perceived inhibition is low (OR= 6.22; 95% CI= 2.21 to 17.46; p= 0.001), and cues to act are high (p= 0.001) statistically significant effect on acceptance of vaccination COVID-19 2nd dose. Conclusion: Community acceptance of COVID-19 dose II vaccination is related to perceptions of vulnerability, perceived severity, perceived benefits, perceived obstacles, and cues to act.